Water scarcity: Institutional change, water markets and privatization - Cesare Dosi; William K. Easter (Fondazione Eni Enrico Mattei (FEEM), 2000)
A number of countries face water shortages because they need to make some basic changes in their water management. Policy options do exist. Most of them share the objective of treating water and water services as an economic good, by regulating private inefficient appropriation of open-access resources, and by making the demand for water less independent of users' willingness to pay for it. The aim of this paper is to provide an overview of these policy options by illustrating their rationale and possible caveats. We begin by stressing the importance of improving countries' social capital (i.e., institutional arrangements and management rules for allocating water between competitive uses). We then concentrate on some economic approaches to improving water management, i.e., the establishment of water markets and the privatisation of water utilities, by focussing on experiences and on-going developments in the United States and the European Union.
Keywords: Q25; Q28; L95; 330; Water resources management; water services; water markets; privatisation; Wassermangel; Wasserpolitik; Privatisierung; Wasserversorgung; USA; EU-Staaten